A Comparative Clinical Study on Matra Basti with Bilva Taila and Mahanarayana Taila in Gridhrasi w.s.r.to Sciatica - Greeshma.K; Gautham Shetty (International Journal of Ayurveda and Pharma Research, 2023)
Panchakarma is a unique therapeutic procedure explained in Ayurveda because of its preventive, promotive and rejuvenative properties as well as providing a radical cure. Charaka and Vaghbata have described Basti as Ardha Chikitsa which itself is self-explanatory about its importance. The cardinal signs and symptoms of Gridhrasi are Sthambha, Ruk, Toda and Spandana starting first in Sphik and radiating to Kati, Prishta, Uru, Janu, Jangha, and Pada. Sciatica, in which neuralgia along the course of sciatic nerve often produces pain, numbness, tingling sensation, radiating from the lower back and upper buttock down the back of the thigh, calf and to the foot. Many of the clinical features of Gridhrasi resemble to that of sciatica. It is statistically estimated that four out of five (80%) of the population is exposed to the back pain lasting for more than a day at sometimes during their life. This reaches peak in 25-50 years of age. Gridhrasi seems to occur with about same time frequency in patient with sedentary occupation as those doing heavy work. Mahanarayana Tailam is considered as one of the best oil to mitigate Vata. Due to Snigdha and Ushna Guna it acts on Vata and Kapha Dosha. In Bilva taila, Bilva having Katu tiktha, Kashaya rasa and Tikshna ushna guna can mitigate Vata kapha vikaras and Bilva is told in Asthapana gana dravya by Acharya charaka and hence can be used in Gridhrasi. So this study is planned to know the comparative efficacy of Bilvataila and Mahanarayana taila matra basti in the management of Gridhrasi. Basti is considered among one of the important treatment procedures in Gridhrasi. Matrabasti being a variety of Sneha Basti, plays a major role in the management of Gridhrasi.